Numerical methods for exterior problems - Ying, Long'an, 1936- (Peking University series in mathematics ;, 2006)
This book provides a comprehensive introduction to the numerical methods for the exterior problems in partial differential equations frequently encountered in science and engineering computing. The coverage includes both traditional and novel methods. A concise introduction to the well-posedness of the problems is given, establishing a solid foundation for the methods. Sample Chapter(s). Chapter 1: Exterior Problems of Partial Differential Equations (1,839 KB). Contents: Exterior Problems of Partial Differential Equations; Boundary Element Method; Infinite Element Method; Artificial Boundary C.